Influence of shift work on cardiovascular disease risk in Southern African long-distance truck drivers: a cross-sectional study. Issue 4 (13th April 2022) - Draaijer, Melvin; Scheuermaier, Karine; Lalla-Edward, Samanta Tresha; Fischer, Alex Emilio; Grobbee, Diederick E; Venter, Francois; Vos, Alinda
Abstract : Objectives: Cardiovascular disease (CVD) is a major problem globally. Truck drivers have an increased risk of CVD due to a sedentary lifestyle, irregular working hours and behavioural choices. We aimed to get insight into the contribution of night shift work to CVD risk in long-distance truck drivers in South Africa. Design: A cross-sectional study. Setting: Enrolment took place at three South African truck stop locations in two provinces; Bloemfontein (Free State), Pomona Road (Gauteng) and Soweto (Gauteng). Participants: 607 males aged ≥18 years with full-time employment as a long-distance truck driver were included. The criteria for inclusion were willingness and being able to provide informed consent and to complete the study procedures. Primary and secondary outcome measures: Information was collected on sociodemographics, occupational and health characteristics. Physical measurements, an ECG and carotid intima–media thickness (CIMT) measurements were taken. A night shift was defined as working at least 3 hours between 22:00 and 6:00 hours once a week. CVD risk was defined with the Framingham Risk Score (FRS), the Atherosclerotic Cardiovascular Disease (ASCVD) risk algorithm, left ventricular hypertrophy (LVH) and CIMT. Results: In total, 607 truck drivers were included of which 305 (50.2%) worked in day shifts only and 302 (49.8%) worked day and night shifts. There was a high prevalence of CVD risk factors in both groups as 33% were hypertensive, 28% obese and 37% had abnormal lipid levels. Working day and night shifts compared with working only day shifts did not result in differences in FRS, ASCVD risk or LVH. No difference was found in CIMT measurements, except for the maximum bulb thickness which was higher in day shift workers. Conclusions: CVD risk factors are considerably present in male truck drivers in South Africa. CVD risk does not differ between dayshift and day–night shift workers in this cross-sectional analysis.